Institutional Conditions of Corporate Citizenship - Jeurissen, Ronald (Journal of business ethics, 2004)
Exploring the concept of citizenship from the history of political philosophy provides suggestions about what corporate citizenship could mean. The metaphor of corporate citizenship suggests an institutional approach to corporate social responsibility. Citizenship is a social role, characterized by an orientation towards the social contract, collective and active responsibility, as well as a positive attitude towards the juridical state. By analogy, corporate citizenship is a social role, characterized by the social contract of business, a participatory ethics of business, the precautionary principle and the promotion of just international institutions. It is considered that corporate citizenship depends on a number of interacting institutional conditions that hold society partly responsible for the social performance of their companies. Finally, the problem of the dissolution of corporate social responsibility is reviewed in an institutional environment where everyone is considered responsible.